Enhancing Science Learning Activities through the Implementation of Discovery Learning and Teaching at the Right Level Method - Irfan Ananda Ismail; Fadhila Ulfa Jhora; Qadriati Qadriati; Munadia Insani (Jurnal Penelitian Pendidikan IPA, 2024)
Education plays a vital role in cultivating qualified future generations, with active student participation serving as an indicator of effective learning processes. Preliminary observations at SMP Negeri 32 Padang revealed low engagement levels in science classes, prompting the need for interventions to boost students' involvement. The primary objective of this classroom action research was to enhance student engagement in science learning activities through implementing the Discovery Learning model and Teaching at the Right Level approach in a Grade 8 classroom at SMP Negeri 32 Padang. The study was conducted over three cycles, each consisting of planning, acting, observing, and reflecting phases. Data on student engagement in science learning activities was collected through observations using a rubric. The initial data in Cycle I revealed low engagement at 36.72%. After implementing interventions integrating Discovery Learning activities and personalized scaffolding based on students' ability levels in Cycles II and III, student engagement progressively increased to 45.76% and 62.28% respectively. Surveys and interviews indicated students found the learner-centered, inquiry-based activities more enjoyable and effective for understanding compared to traditional instruction. The findings demonstrate the potential of combining Discovery Learning and Teaching at the Right Level methods to significantly improve learning participation by stimulating intrinsic motivation through autonomous exploration while providing individualized support. The research offers practical strategies for enhancing science education engagement and contributes to the Kurikulum Merdeka goals of fostering participatory, flexible learning environments tailored to students' unique needs